2019
DOI: 10.24908/pceea.vi0.13881
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Integrating Indigenous Knowledges and Perspectives in Engineering Curricula on Students’ Learning: The Development of a Classroom Case Study

Abstract: Indigenous Peoples in Canada have practiced sustainability for centuries. Their knowledges, perspectives and design principles are applicable on both a local and global scale especially in our quest to find sustainable approaches to food security, energy independence, and climate change impacts. However, the opportunities for Indigenous Peoples to fully participate and formally offer knowledge and guidance on sustainable development in engineering education have been limited. Engineering training in Canada req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The changes needed to Indigenize curriculum will be and should be unique to each program, dependent on the consultation with the Indigenous Peoples and their communities that are located in that place. This view that educators must collaborate with local Indigenous Peoples to develop an engineering curriculum that is representative of their community is prevalent throughout the literature, and several studies have reported on these collaborative initiatives (e.g., Mante et al 2019;Goldfinch and Kennedy 2013). Mante et al (2019) designed a study to assess the impact on students' learning after a lecture about consultation with Indigenous communities during infrastructure development from the perspective of a local Elder.…”
Section: Consultation and Collaboration With Indigenous Peoples And C...mentioning
confidence: 99%
See 3 more Smart Citations
“…The changes needed to Indigenize curriculum will be and should be unique to each program, dependent on the consultation with the Indigenous Peoples and their communities that are located in that place. This view that educators must collaborate with local Indigenous Peoples to develop an engineering curriculum that is representative of their community is prevalent throughout the literature, and several studies have reported on these collaborative initiatives (e.g., Mante et al 2019;Goldfinch and Kennedy 2013). Mante et al (2019) designed a study to assess the impact on students' learning after a lecture about consultation with Indigenous communities during infrastructure development from the perspective of a local Elder.…”
Section: Consultation and Collaboration With Indigenous Peoples And C...mentioning
confidence: 99%
“…This view that educators must collaborate with local Indigenous Peoples to develop an engineering curriculum that is representative of their community is prevalent throughout the literature, and several studies have reported on these collaborative initiatives (e.g., Mante et al 2019;Goldfinch and Kennedy 2013). Mante et al (2019) designed a study to assess the impact on students' learning after a lecture about consultation with Indigenous communities during infrastructure development from the perspective of a local Elder. This work is presently underway, but preliminary findings demonstrated the profound impact the Elder's visit had on the students who agreed to participate in the study (Thomsen et al 2021;Kilada et al 2021).…”
Section: Consultation and Collaboration With Indigenous Peoples And C...mentioning
confidence: 99%
See 2 more Smart Citations